Improving student outcomes IPAS using Learning Together assisted Smart Apps Creator grade IV SDN 27 Anak Air Padang - Nora Suraya; Hamimah (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to improve students’ learning outcomes in IPAS (Integrated Science, Mathematics, and Social Studies) learning by using the Learning Together model assisted by Smart Apps Creator (SAC). The background of this study is the low learning outcomes, student activity, and engagement triggered by an ineffective learning process, resulting in suboptimal learning outcomes in Grade 4 at SDN 27 Anak Air, Padang City. The research method used was Classroom Action Research (CAR) with a qualitative and quantitative approach. The implementation of this study consisted of two cycles comprising the planning, implementation, observation, and reflection stages. The subjects of this study were the teacher and fourth-grade students of SDN 27 Anak Air, comprising 27 students—10 boys and 17 girls. Data collection techniques included observation, interviews, documentation, and assessment of learning outcomes. The results of the study showed an increase from an average of 68 to 77 in Cycle I and a further increase in Cycle II to 89.59. In line with this, the learning process also improved in terms of both the teacher and the students. Thus, it can be concluded that the application of the Learning Together Model assisted by Smart Apps Creator (SAC) can encourage students to be more active and participate in learning, which has an impact on improving learning outcomes.